First metatarsophalangeal joint arthrodesis with two orthogonal two hole plates - Muhammad Ali Fazal; Jason Hol-Ming Wong; Luthfur Rahman (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: First MTP joint fusion is a reliable procedure for advanced arthritis for the first MTP joint. There are many techniques described. The purpose of our study is to report clinical, radiological, functional outcomes and complications of first metatarsophalangeal joint fusion with hand preparation of the joint and fixation with two orthogonal locking plates without a compression screw. Methods: 32 feet in 26 consecutive patients under went first metatarsophalangeal joint fusion with above technique. There were 23 women and 3 men. Mean age was 64 years and mean follow-up was 49 months. 21 patients had osteoarthritis, 10 had rheumatoid arthritis and one had psoriatic arthritis. Clinical, radiological, American Orthopaedic Foot and Ankle Score and Foot and Ankle Disability Index clinical rating scales were used for evaluation. Results: Fusion was achieved in 27 feet. The incidence of radiological non-union was 15.7%. Mean AOFAS score improved from 37.1 to 80.7 (p < 0.0001) and mean FADI score improved from 40.3 to 86.9 postoperatively (p < 0.0001). Two patients with osteoarthritis and three with Rheumatoid arthritis did not unite. Four of these patients were managing hence revision surgery was not carried out but had low AOFAS and FADI scores. One patient with symptomatic non-union declined further surgery. One patient needed plate removal for a low grade infection and reoperation rate was 3.1%. Conclusions: In our experience, first metatarsophalangeal joint arthrodesis using two orthogonal two hole plates without a compression screw is associated with a higher non-union rate in our cohort hence we do not recommend this technique. Level of evidence: Level IV, therapeutic study. Keywords: First metatarsophalangeal fusion, Plates, Non union, Fusion, AOFAS